DEVELOPMENT OF MONETARIST THEORIES AND THEIR IMPACT ON MONETARY REGULATION - Вовчак, Ольга; Мельник, Тетяна (Socio-economic relations in the digital society, 2019)
The article examines the history of the development of the monetarist theories and the monetary regulation, describes the characteristics of various economic schools, defines their contribution to the development of economic theory and highlights the main ideas, defines the place of monetarist theories in the theory of money, classifies theories in accordance with the history of their emergence and the main provisions, defines the main differences between scientific approaches. The advantages and disadvantages of the main monetarist theories are considered, depending on certain stages of development of economic thought: from their historical origin to the present, because the achievements of each theory have a huge impact on our present and practice of monetary regulation by the central banks. Monetary policy and monetary regulation of the central banks are largely based on monetarism and its modern interpretation. Therefore, the article focuses on the history of the development of these monetarist theories, in addition, theories preceding their emergence are considered. Monetary regulators are aware of the need to use the positive experience of other theories, since the manifestations of financial crises have highlighted the need for changes to existing monetarist monetary control approaches based on monetarism and its current trends. This forces the central banks of many countries to look for non-standard monetary regulation instruments and use innovative methods along with historically proven approaches to combining state and market regulation of the economy. Based on the conducted research, it was suggested to use the most acceptable postulates of various economic theories and schools that should be taken into account when conducting monetary policy and monetary regulation by central banks and the National Bank of Ukraine.